2017
DOI: 10.1016/j.jff.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Coacervates of whey proteins to protect and improve the oral delivery of a bioactive molecule

Abstract: a b s t r a c tThe potentiality of heteroprotein complex coacervates as biocarrier for a bioactive was investigated. Vitamin B9 (B9), also known as folic acid, was encapsulated by complex coacervation of two whey proteins (WP), b-lactoglobulin and lactoferrin. The stability and bioavailability of formed B9-WP coacervates was then characterized. Under degradative conditions in vitro (UV light irradiation, and oxidation by H 2 O 2 ), WP coacervates protected the vitamin against chemical degradation. B9-WP coacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 51 publications
0
7
0
2
Order By: Relevance
“…Recent studies showed that complex coacervation could be used by mixing two oppositely charged proteins with an affinity for an encapsulated bioactive component [ 106 ]. Efficient encapsulation yield with a protective effect was reported for vitamin B9 encapsulated in milk-derived protein coacervates.…”
Section: Stability and Encapsulation Of Eosmentioning
confidence: 99%
“…Recent studies showed that complex coacervation could be used by mixing two oppositely charged proteins with an affinity for an encapsulated bioactive component [ 106 ]. Efficient encapsulation yield with a protective effect was reported for vitamin B9 encapsulated in milk-derived protein coacervates.…”
Section: Stability and Encapsulation Of Eosmentioning
confidence: 99%
“…These types of materials have the advantage of allowing for fully-aqueous processing, and have been used broadly for protein purification, with coacervates finding particular utility in delivery. [45][46][47][48][49][50] Furthermore, the phase-separated nature of these materials allows for strong partitioning of proteins into the polymeric phase, allowing for the easy preparation formulations with a high encapsulation and/or loading of protein. [12,[51][52][53] These high levels of incorporation are mainly due to the electrostatics and entropic gains associated with phase separation, but also take advantage of differences in the overall polarity of the coacervate environment compared to pure water.…”
Section: The Challenge Of Protein Encapsulationmentioning
confidence: 99%
“…Complex coacervation, [49,51,52,56,57,[61][62][63][64][65][66][67][68][69][70][71][72][73] whose characteristics mimic the characteristics of cells, is a simple, purely aqueous strategy for encapsulating proteins. Complex coacervation is a liquid-liquid phase separation phenomenon resulting from the association of two oppositely charged macro-ions (e.g., polymer, protein, surfactant micelles).…”
Section: Complex Coacervation Phase Behavior and Biomimicrymentioning
confidence: 99%
“…Finally, heteroprotein systems that undergo complex coacervation are also of great interest to the field [48,64,65,66]. These multi-protein coacervates are particularly relevant to the formation and biological function of membraneless organelles [67,68].…”
Section: Macrophase Separation Of Protein–polyelectrolyte Complexesmentioning
confidence: 99%